Musalima citrakalā - Hasan, Sayed Mahmudul (Bāṃlā Ekāḍemī, 1979)
History of the development of Muslim painting; with an analysis of the socioreligious basis and impact of eastern and western influences on the evolution of the art in the Muslim countries.